Job Autonomy and Education-Skill Matches of Immigrant Workers in Germany - Beyer, Robert C.M. (Taylor and Francis, 2019)
This letter examines the determinants of occupational autonomy and education-skill matches of immigrant workers in Germany. Their jobs are characterized by much lower autonomy than those of comparable natives and the immigrant penalty decreases only minimally over time. In contrast to wages, the difference between immigrants from advanced and non-advanced countries is small. But immigrants from advanced countries are much more likely to have a job matching their qualification. The probability of a match does not increase over time for highly educated immigrants, but does for others. Highly educated immigrant women have an additional disadvantage. In some industries low autonomy and skill downgrading of immigrant workers are particularly common.